2023
DOI: 10.2174/1389202924666230207111530
|View full text |Cite
|
Sign up to set email alerts
|

An Insight into Emerging Begomoviruses and their Satellite Complex causing Papaya Leaf Curl Disease

Abstract: Papaya leaf curl disease (PaLCD) was primarily detected in India and causes major economic damage to agriculture crops grown globally, seriously threatening food security. Begomoviruses are communicated by the vector Bemisia tabaci, and their transmission efficiency and persistence in the vector are the highest, exhibiting the widest host range due to adaptation and evolution. Symptoms induced during PaLCD include leaf curl, leaf yellowing, interveinal chlorosis, and reduced fruit quality and yield. Consequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 106 publications
0
2
0
Order By: Relevance
“…Begomoviruses exhibit a wide range of species or strains with diverse biological characteristics, including pathogenicity [44,45]. As reported by Saxena et al, 1998 a novel begomovirus species named PaLCuV was initially identified and categorized within the Geminiviridae family [46].…”
Section: Discussionmentioning
confidence: 98%
“…Begomoviruses exhibit a wide range of species or strains with diverse biological characteristics, including pathogenicity [44,45]. As reported by Saxena et al, 1998 a novel begomovirus species named PaLCuV was initially identified and categorized within the Geminiviridae family [46].…”
Section: Discussionmentioning
confidence: 98%
“…Begomoviruses have a fairly simple structural makeup, yet their evolutionary history is quite complicated. The bipartite form of begomoviruses has been largely overlooked in evolutionary research, despite the fact that characteristics related to begomovirus-host interactions and viral evolutionary dynamics have been well investigated [33,34]. According to some research, the evolutionary histories and selection pressures that the DNA-A and DNA-B components have encountered may differ.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been conducted to ascertain the evolutionary dynamics of begomoviruses; however, these studies have been First report of Tomato leaf curl New Delhi virus (a bipartite begomovirus) from round gourd plant in Swat region of Pakistan: its phylogenetic and biogeographic analysis You're reading als predicated on the analysis of the bipartite begomoviruses' DNA-A component. Because the DNA-B component of these viruses plays a significant role in the viral infectious cycle, it is imperative to take this component's evolution into account as well [33,34]. Here, we successfully completed a simultaneous evolutionary investigation of the bipartite begomoviruses' DNA-B and DNA-A components.…”
Section: Discussionmentioning
confidence: 99%
“…The disease is characterized by the curling and distortion of the leaves, stunted growth, and reduced fruit yield. PaLCuD infection has resulted in significant yield losses, which range from 40 to 100% which has been reported in the United States and Mexico ( Alabi et al, 2016 ; Alcala-Briseno et al, 2020 ; Srivastava et al, 2023 ). Infected plants may also exhibit yellowing of the leaves and a general decline in health.…”
Section: Introductionmentioning
confidence: 99%
“…Current management strategies involve several implementations related to integrated pest management strategies. These involve whitefly control, planting resistant varieties, removing, and destroying infected plants, proper cultural practices, monitoring, and early detection ( Srivastava et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%